2023
DOI: 10.1021/acs.jafc.3c03871
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Enhanced Thermostability and Catalytic Activity of Xylanase from Streptomyces rameus L2001 by Rigidifying Flexible Regions in Loop Regions of the N-Terminus

Qiuhua Wu,
Chengnan Zhang,
Wenqi Dong
et al.

Abstract: The GH11 xylanase XynA from Streptomyces rameus L2001 has favorable hydrolytic properties. However, its poor thermal stability hinders its widespread application in industry. In this study, mutants Mut1 and Mut2 were constructed by rationally combining the mutations 11 YHDGYF 16 , 23 AP 24 / 23 SP 24 , and 32 GP 33 . The residual enzyme activity of these combinational mutants was more than 85% when incubated at 80 and 90 °C for 12 h, and thus are the most thermotolerant xylanases known to date. The reduced fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
(167 reference statements)
0
7
0
Order By: Relevance
“…The molecular-docking findings were validated through an additional 100 ns of molecular-dynamics simulations. The root-mean-square deviation (RMSD), a pivotal parameter for assessing conformational fluctuations within the protein–ligand complex, inversely correlates with complex stability [ 46 ]. Notably, during the 60–100 ns period, the RMSD values of C10-HSL-SdiA_EcN exhibited lower values compared with C10-HSL-SdiA_K12, implying heightened thermal stability within the C10-HSL-SdiA_EcN complex ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular-docking findings were validated through an additional 100 ns of molecular-dynamics simulations. The root-mean-square deviation (RMSD), a pivotal parameter for assessing conformational fluctuations within the protein–ligand complex, inversely correlates with complex stability [ 46 ]. Notably, during the 60–100 ns period, the RMSD values of C10-HSL-SdiA_EcN exhibited lower values compared with C10-HSL-SdiA_K12, implying heightened thermal stability within the C10-HSL-SdiA_EcN complex ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it was reported that a larger substrate-binding channel leads to higher enzyme activity . In a previous study, mutation in the GH11 xylanase XynA causes crack propagation near the catalytic pocket and results in enhanced enzyme activity . In summary, a more open catalytic cleft appeared to facilitate substrate access to the active pocket and led to a higher catalytic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, simulations of 100 ps each are performed in the NVT and NPT ensembles, followed by MD simulations for 50 ns at 300, 330, and 360 K, respectively. By analyzing atomic trajectories, data on root-mean-square deviation (RMSD), solvent-accessible surface area (SASA), root-mean-square fluctuation (RMSF), and radius of gyration (RG) are generated. , …”
Section: Methodsmentioning
confidence: 99%